From Rome to New York background to the urban proposals of Le Corbusier - Daza, Ricardo (Journal of Architecture and Urbanism, 2016)
The paper argues that urban proposals of Le Corbusier arise from the study of the history of architecture. Through a comparison of his journey impressions with his urban projects, this paper demonstrates that the ideas and perceptions that determined Le Corbusier proposals were extracted and interpreted from the study that the young architect carried out of the settlements and cities of Eastern Europe and the Mediterranean in his well-known Voyage d’Orient.